2016
DOI: 10.1007/s00701-016-2842-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of carotid artery stenosis using histological specimens: a comparison of CT angiography, magnetic resonance angiography, digital subtraction angiography and Doppler ultrasonography

Abstract: CTA yields the best accuracy in detection of carotid stenosis, provided that all axial slices of the stenosis are checked and carefully analysed. DSA underestimates moderate and mild ICA stenosis, whereas DUS overestimates high-grade ICA stenosis. For MRA, a relatively low correlation coefficient was observed with histological findings. We conclude that CTA-ecst technique is the most reliable technique for carotid stenosis measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…However, when a large vessel has a moderate stenosis between 50–69% these non-invasive techniques have a lower sensitivity and specificity for the accurate detection of the degree of stenosis. 6671 In recent years, there are no comparative studies of the two modalities with DSA in any large series of patients. A recent review that included previous and more contemporary studies of reported sensitivity and specificity for CTA of 81.7% and 85.6%, that may be lower than those reported for contrast-enhanced MRA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when a large vessel has a moderate stenosis between 50–69% these non-invasive techniques have a lower sensitivity and specificity for the accurate detection of the degree of stenosis. 6671 In recent years, there are no comparative studies of the two modalities with DSA in any large series of patients. A recent review that included previous and more contemporary studies of reported sensitivity and specificity for CTA of 81.7% and 85.6%, that may be lower than those reported for contrast-enhanced MRA.…”
Section: Resultsmentioning
confidence: 99%
“…[66][67][68][69] However, when a large vessel has a moderate stenosis between 50-69% these non-invasive techniques have a lower sensitivity and specificity for the accurate detection of the degree of stenosis. [66][67][68][69][70][71] In recent years, there are no comparative studies of the two modalities with DSA in any large series of patients.…”
mentioning
confidence: 99%
“…In contrast with some other studies which utilized CT angiography, we used cervical contrast MDCT and our diagnostic modality could be assumed as a potential limitation for estimating severity of CAS, but correlation of CT angiography with conventional angiography has shown to be strong, even better than Doppler ultrasonography. [27][28][29] Results of Doppler Ultrasound (DUS), magnetic resonance angiography (MRA), CT angiography (CTA) and digital subtraction angiography (DSA) with histopathology of atherosclerotic specimen have been Compared by Netuka et al, 30 and they found significant accuracy for each of these diagnostic modalities but the strongest correlation was observed for CTA. Although there are some papers in agreement with good correlation of CTA and DUS, 31,32 but there are some studies which shows underestimation of stenotic severity by CT comparing to DUS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ultrasonographic data cannot compared with other imaging form like computed tomography angiography, magnetic resonance angiography or digital subtraction angiography. The Duplex ultrasonography may overestimate the degree of stenosis (34). However, any disagreement about the results was resolved by specialist team.…”
Section: Discussionmentioning
confidence: 99%